Word-Connecting Games on St Ignasius Junior High School Students' Vocabulary Improvement in Medan - Idawati Waruwu; Asri Rafica Silalahi; Susi Santi Sinaga; Herliaman Lafau (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2022)
This study intends to determine whether word-connecting games can help students in class VII at SMP St. Ignasius Medan improve their practice of English vocabulary. According to the Kemmis and McTaggart models, this study is a class action study that was carried out in two cycles. All 21 students in class VIIc, with a breakdown of 12 men and 9 women, served as the study's subjects. Tests are used to gauge students' English vocabulary proficiency, and observation sheets are used to gauge how well word-continuing game techniques, which involve teacher and student activities, are used. According to the study's findings, using the word-connecting games method significantly increased students' ability to learn and comprehend English vocabulary. Researchers' findings show a 70 percent increase in English vocabulary from cycle I to cycle II and a 90 percent increase from cycle I to cycle II.